The investigation of the tensile and quasi-static indentation properties of pineapple leaf / kevlar fibre reinforced hybrid composites - Ng, Lin Feng; Dhar Malingam, Sivakumar; Subramaniam, Kathiravan; Selamat, Mohd Zulkefli; Woo, Xiu Juan (Science and Technology Research Institute for Defence, 2020)
Fibre reinforced polymers are the contemporary advanced materials that possess high specific properties when compared to metallic alloys. They have been widely explored since the past few decades. This research study intends to investigate the quasi-static indentation behaviour of nonhybrid and hybrid pineapple leaf / Kevlar fibre reinforced composites with various stacking configurations. Four fibre stacking configurations were fixed in the composite laminates. The composite panels were fabricated through hot moulding compression process. Quasi-static tensile and indentation test were then conducted to measure the tensile properties, energy absorption, maximum indentation force and specific energy absorption of the non-hybrid and hybrid composites. The front and rear fracture surface of the non-hybrid and hybrid composites were analysed after the indentation test. The findings evidenced that the hybrid pineapple leaf / Kevlar fibre reinforced composites showed a positive hybrid effect where the tensile properties, maximum indentation force and energy absorption were drastically improved after partial incorporation of Kevlar fibre in the composites. However, the hybrid composites with the outermost Kevlar fibre and middle pineapple leaf fibre showed comparable tensile and indentation properties to the non-hybrid Kevlar fibre reinforced composites. The results demonstrated the high potential of hybrid pineapple leaf / Kevlar fibre reinforced composites in the replacement of non-hybrid Kevlar fibre reinforced composites.